The effects of obesity on thyroid function in a metabolically healthy high-fat, high-carbohydrate diet-induced obese rat model - Pather, Reveshni; Khathi, Andile; Ngubane, Phikelelani (Frontiers in Endocrinology, 2025)
IntroductionObesity is a recognized exacerbator of thyroid dysfunction due to its detrimental effects on energy homeostasis, appetite regulation, basal metabolic rate, thermogenesis, and metabolism. However, almost all the reported findings on obesity-related thyroid dysfunction are based on models of metabolically unhealthy obesity (MUO) in the presence of insulin resistance. There are currently no reported studies using a metabolically healthy obesity (MHO) model characterized by the absence of insulin resistance to investigate thyroid dysfunction. Hence, this study aimed to investigate the association between thyroid dysfunction and obesity in a metabolically healthy high-fat high-carbohydrate diet-induced obese rat model.Materials and methodsMale Sprague Dawley rats were randomly divided into either the control diet or the high-fat high-carbohydrate diet group (HFHC) (n=9, per group). During the 5-month induction period, the control group did not develop obesity while consuming a standard diet with water. The HFHC diet group consumed the HFHC diet and water for the same duration and was diagnosed with obesity. Post-obesity confirmation, the animals continued with the respective diets for a further 7 months to maintain the obese state. Caloric intake, fasting blood glucose (FBG) and BMI were measured once a month for the duration of the experiment. Glucose homeostasis and thyroid functional parameters were assessed terminally, accompanied by satiety and pro-inflammatory markers.ResultsThe HFHC diet group presented with higher BMI, caloric intake and FBG, and elevated insulin, HOMA-IR, Hb1Ac, leptin and IL-6 levels compared to the control diet group. The HFHC diet group presented with significantly elevated levels of TSH, fT3 and fT4. These observations suggest that thyroid homeostasis is disturbed in the obese state. However, the reported elevated glycemic status indicators and IL-6 concentrations in the HFHC diet group did not satisfy the minimum criteria to be characterized as MUO.ConclusionThe HFHC diet has induced MHO in male Sprague Dawley rats. This warrants using this model to investigate the homeostatic changes that occur during the metabolically healthy obese state. This can open new avenues for developing preventative measures to avoid progressing to MUO.